Enterococcal urinary tract infections in a university hospital: clinical studies - Barros,Milton (2009)
Although urinary tract infections (UTI) represent the most common infection caused by enterococci, some aspects remain to be fully clarified. The aim of this study was to determine the clinical characteristics present in UTI caused by Enterococcus spp. in patients followed up at the Prof. Edgard Santos Teaching Hospital of the Federal University of Bahia. All patients consecutively examined between 1997 and 2005, who received a diagnosis of UTI caused by Enterococcus spp. were included in the study. UTI was defined as the presence of 10(5) colony-forming units per mL of urine. Standard microbiological techniques were used. During the study period, 6.2% of the urine cultures were positive for Enterococcus spp. The mean age of the patients was 48.9 years and 57% were male. At initial evaluation, 13% of the patients had complaints suggestive of UTI. Nineteen patients had a history consistent with obstructive uropathy and 26 with neurogenic bladder. At final evaluation, UTI was the diagnosis in 48 patients. In 36 patients (29%), the primary diagnosis was related to urogenital diseases, consisting of obstructive uropathy in 23 of these cases, while in 32 patients (25.8%) primary diagnosis was related to neurologic diseases, frequently neurogenic bladder. UTI caused by Enterococcus spp. is not infrequent, is usually associated with few or no symptoms and occurs in sick patients who have anatomical or functional obstructive uropathy associated or not with urinary tract catheterization or instrumentation. The diagnosis of enterococcal UTI may indicate a urinary tract abnormality yet to be diagnosed.